(untitled) (Islas, 2023)
Introduction: The objective of this study is to analyze the zoomorphisms collected in the Léxico Mayor de Cuba, as well as the polysemy of animal referents and elements of phraseological technique by Rodríguez Herrera related to the treatment of phraseological variation. Methods: With a broad conception of phraseology, the Léxico Mayor de Cuba was examined and subsequently compared with the database of Cuban Spanish prepared for the doctoral thesis The variation of zoomorphic phraseological units in the Spanish of Cuba and Spain. Results: Zoomorphisms are lemmatized in three different ways, with the definition often provided through a phraseological synonym. This is complemented by diatopic variants, usage examples, and pragmatic information. Out of the 322 zoonyms identified, nearly 25% have more than one meaning, which can be botanical, metaphorical, or refer to objects, and even to other animals. Conclusions: Zoonyms are highly productive referents in phraseology. Many of those compiled by Rodríguez Herrera are part of currently used expressions in Cuba, and polysemy complicates their analysis, translation, and lemmatization in phraseological or general works.